Antioxidative and hepatoprotective effects of Artemisia absinthium L. hydroalcholic extract in rat - Mohammadian Ali; Moradkhani Shirin; Ataei Sara; Heidary Shayesteh Tavakol; Sedaghat Mahsa; Kheiripour Nejat; Ranjbar Akram (Journal of HerbMed Pharmacology, 2016)
Introduction: Artemisia absinthium L. (AA) is a large, diverse genus of the family Asteraceae. AAhas long been used as customary herbal medicine in world for the treatment of gastric pain, cardiacstimulation, improvement of memory and for the restoration of declined mental function. The aimof present study was to evaluate the hepatoprotective effects of AA on some factors ref lecting thedevelopment of oxidative toxic stress in plasma.Methods: Twenty male rats were equally divided in to 4 groups (5 rats each). Group I actedas control (received normal salin). Treatment groups were II, III and IV which were givenArtemisia 10, 50 and 100 mg/kg/day respectively only by gavage for 24 hours. After treatment,blood specimens were collected. Liver enzymes such as aspartate aminotransferase (AST) andalanine aminotransferase (ALT) with total antioxidant power (TAP) and total thiol groups (TTG)concentrations were measured.Results: Levels of ALT, AST and TTG were decreased in the group II compared to the control(group I). ALT and AST in 50 mg/kg group was observed compared with control group. Also, TTGincreased in Artemisia 50 mg/kg group compared to control group.Conclusion: Results suggests that alcoholic extract of Artemisia can ameliorate liver toxicity inrats through reducing the serum levels of ALT, AST, and oxidative damage.